Upconversion luminescence properties of Y2O3: Yb3+/Er3+/Tm3+ nanocrystal doped PMMA nanocomposites - Tabanli, Sevcan; Eryurek, Gonul (Elsevier BV, 2019)
Abstract Y2O3 nanocrystals triply doped with Yb3+, Er3+, Tm3+ ions were synthesized via alginic acid-assisted gelation using thermal decomposition method and annealed at 800 °C for 24 h. Nanopowders were embedded into PMMA matrix via free-radical polymerization in an ultrasonic bath. X-ray diffraction and transmission electron microscopy measurements have shown that the crystal grain sizes decreased significantly with the narrow size distributions of the nanocrystals in PMMA matrix. A diode laser at 975 nm was used to measure the upconversion luminescence of the annealed nanopowders and those embedded in PMMA between the 400–850 nm wavelength region. The Er3+ concentration and the excitation power density dependencies of the relative intensities for red, green and blue upconversion luminescence in the nanopowder and PMMA nanocomposites are found to be different. The measured CIE-1931 color coordinates of the upconversion luminescence in PMMA nanocomposites show appreciable color stability under different excitation power densities, which is required for potential applications in the field of photonics.